Persepsi Mahasiswa Teknik Informatika terhadap Pembelajaran Matematika Diskrit Secara Daring - Ayu Ismi Hanifah (Jurnal Halaqah, 2022)
The Covid-19 pandemic causes changes that have happened, particularly in the education sector. To make education perform properly, the Government issued policies to education scope to be flexible in choosing a curriculum that appropriates the students’ learning needs. In this case, online learning can be an alternative that can be used to maintain learning operating well. The purpose of this study was that the researcher wanted to look at Informatics Engineering students’ perception of discrete mathematics learning conducted online. The method used was a qualitative research method. The subjects in this study were three classes of 1st-semester Informatics Engineering students who were receiving discrete mathematics material. The research data were obtained from questionnaires filled out by students online via Google Form. The results of this study included 1) Informatics Engineering students agreed with online discrete mathematics effectiveness learning, 2) Informatics Engineering students’ easiness perception in accessing the internet when they got discrete mathematics learning online felt easy, 3) students felt they understood the material obtained during online discrete mathematics learning, and 4) Informatics Engineering students felt happy with this online discrete mathematics learning.